Ask Question
5 July, 05:09

Simplify.

Rewrite the expression in the form 4^n

(4^6) (4^-8) =

+2
Answers (1)
  1. 5 July, 07:05
    0
    4^-2

    Step-by-step explanation:

    The rules of exponents tell you ...

    (a^b) (a^c) = a^ (b+c)

    This means ...

    (4^6) (4^-8) = 4^ (6-8) = 4^-2
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Simplify. Rewrite the expression in the form 4^n (4^6) (4^-8) = ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers